Afterword. The Consumer’s Society in the Era of the Post Globalization - Carles Carreras i Verdaguer; Sergi Martínez-Rigol; Alejandro Morcuende González (Bollettino della Società Geografica Italiana)
The article tries a general overview of the contemporary changes in the global economy. First proposes a characterization of the present period of history, advancing some of his main explanatory elements. Next, summarizes the great economic, social, political and cultural changes, discussed on the long way of more than twenty years of research at an international level. Third, it remarks some concrete changes at an urban scale. Finally, suggests the possibilities of some differential urbanization processes, on the way of the planetary urbanization.